2013
DOI: 10.4049/jimmunol.1300479
|View full text |Cite
|
Sign up to set email alerts
|

IL-17RA Is Essential for Optimal Localization of Follicular Th Cells in the Germinal Center Light Zone To Promote Autoantibody-Producing B Cells

Abstract: Germinal centers provide a microenvironment that promotes and regulates the interactions of B-cells with follicular T-helper cells (TFH). Here we show that there are significantly higher frequencies of CXCR5+ICOS+TFH cells in autoimmune BXD2 mice, and these cells express both interleukin (IL)-21R and IL-17RA. Although IL-17 and IL-21 are both important for the formation of spontaneous GCs and development of pathogenic autoantibodies, IL-21, but not IL-17, is required for the proper development of TFH cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 51 publications
(90 reference statements)
7
115
1
Order By: Relevance
“…Moreover, in agreement with high levels of IgG2 in the blood of TGF-βR-KO mice (28), we noticed that Tfh cells that developed in an unrestrained manner in the absence of TGF-β control massively produced IFN-γ in contrast to basal Tfh cells from TGF-βR-WT mice (Supplemental Figure 1C). Furthermore, we did not detect IL-17 (data not shown), a cytokine that has been implicated in pathogenic GC formation in some circumstances (31). jci.org Volume 124 Number 10 October 2014 CD44 hi , CD122, and Ly49 that have been shown to repress spontaneous development of Tfh cells by inducing their apoptotic death, thereby efficiently contributing to the control of autoimmune diseases in both mice and humans (20,21,37).…”
Section: Tgf-β Signaling In T Cells Prevents Aberrant Accumulation Ofmentioning
confidence: 85%
“…Moreover, in agreement with high levels of IgG2 in the blood of TGF-βR-KO mice (28), we noticed that Tfh cells that developed in an unrestrained manner in the absence of TGF-β control massively produced IFN-γ in contrast to basal Tfh cells from TGF-βR-WT mice (Supplemental Figure 1C). Furthermore, we did not detect IL-17 (data not shown), a cytokine that has been implicated in pathogenic GC formation in some circumstances (31). jci.org Volume 124 Number 10 October 2014 CD44 hi , CD122, and Ly49 that have been shown to repress spontaneous development of Tfh cells by inducing their apoptotic death, thereby efficiently contributing to the control of autoimmune diseases in both mice and humans (20,21,37).…”
Section: Tgf-β Signaling In T Cells Prevents Aberrant Accumulation Ofmentioning
confidence: 85%
“…GCs from BXD2 mice have increased numbers of plasmablasts, expression of B cell differentiation genes, and T FH populations. B cell and T cell abnormalities in this strain are rescued by gene deletion of Rgs13 or Rgs16, respectively, which is accompanied by significantly reduced numbers of B-T cell conjugates in GCs and autoantibody titers (71,72). Given RGS13's ability to blunt chemokine-mediated migration, these studies suggest that IL-17 promotes autoimmunity in BXD2 mice by prolonging transit of B and T cells through GCs, resulting in excess antibody production.…”
Section: Rgs13mentioning
confidence: 96%
“…The authors argued that IL-17 induced regulator of G-protein signaling proteins, which suppressed migration, and consequently stabilized germinal center (GC) B cells to elicit proper GC reaction [11,12]. In line with this, it was reported that Th17 cells transferred into wild type (WT) C57BL/6 mice induced GC formation, which was abrogated in IL-17 RA knockout (KO) mice [13].…”
Section: Introductionmentioning
confidence: 94%
“…Xie and colleagues [11,12] reported the first evidence that IL-17 affected antibody production by B cells in an autoimmune BXD2 mouse model. The authors argued that IL-17 induced regulator of G-protein signaling proteins, which suppressed migration, and consequently stabilized germinal center (GC) B cells to elicit proper GC reaction [11,12].…”
Section: Introductionmentioning
confidence: 99%